The Euro Zone Sovereign Debt Crisis and Potential Solutions - Simona Moagăr-Poladian (Revista de Economie Mondială, 2011)
The debt sustainability is a challenging problem to some Eurozone countries, being a reflection of a high rate of unbalanced financial sector. The public debt crisis has already delayed the economic growth of certain countries and will cause unpleasant effects in the near future. Programmes of fiscal consolidation have been applied in each of Eurozone countries, focussed primarily on the banking system in order to prevent banks from bankruptcy. The main objective of the European Commission is to strengthen the trust in the European banking system. The proposals have been oriented toward increasing banking capital on future in concordance to Basel III agreement. By creating of a new governance framework and a new Single Regulatory Act for the whole European banking system it would stimulate the consolidation of the whole banking system from EU.